A Novel Therapeutic Mechanism of Imipridones ONC201/ONC206 in MYCN-Amplified Neuroblastoma Cells via Differential Expression of Tumorigenic Proteins - El-Soussi, Sarra; Hanna, Reine; Semaan, Hanna; Khater, Amanda-Rose; Abdallah, Jad; Abou-Kheir, Wassim; Abou-Antoun, Tamara (Frontiers in Pediatrics, 2021)
Neuroblastoma is the most common extra-cranial nervous system tumor in children. It presents with a spectrum of clinical prognostic measures ranging from benign growths that regress spontaneously to highly malignant, treatment evasive tumors affiliated with increased mortality rates. MYCN amplification is commonly seen in high risk neuroblastoma, rendering it highly malignant and recurrence-prone. In our current study, we investigated the therapeutic potential of small molecule inducers of TRAIL, ONC201 and ONC206, in MYCN-amplified IMR-32 and non-MYCN-amplified SK-N-SH human neuroblastoma cell lines. Our results exhibit potent anti-tumor activity of ONC201 and ONC206 via a novel inhibition of EGF-induced L1CAM and PDGFRβ phosphorylation in both cell lines. Drug treatment significantly reduced cellular proliferation, viability, migration, invasion, tumorsphere formation potential and increased apoptosis in both cell lines. The protein expression of tumorigenic NMYC, Sox-2, Oct-4, FABP5 and HMGA1 significantly decreased 48 h post drug treatment, whereas cleaved PARP1/caspase-3 and H2AX increased 72 h post drug treatment, compared to vehicle-treated cells in the MYCN-amplified IMR-32 cell line. We are the first to report this novel differential protein expression after ONC201 or ONC206 treatment in human neuroblastoma cells, demonstrating an important multi-target effect which may yield added therapeutic benefits in treating this devastating childhood cancer.